2020
DOI: 10.1002/ijc.33009
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a stromal immune phenotype classifier for predicting immune activity and prognosis in triple‐negative breast cancer

Abstract: Our study aims to construct a prognosis-related immune phenotype classifier for predicting clinical prognosis and immune activity in triple-negative breast cancer (TNBC). A total of 237 patients with TNBC from Sun Yat-sen University Cancer Center (SYSUCC) and 533 patients with TNBC from public datasets were included in our study. A stromal immune quantified index was generated with a LASSO Cox regression model based on five prognosis-related immune cells evaluated by CIBERSORT or IHC and was used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 38 publications
4
37
0
Order By: Relevance
“…[47][48][49] The immune microenvironment can exert great influence on the progression of breast cancer, which results in the different clinical prognosis of patients. [50][51][52] We found that patients with TNBC and HER2 overexpression breast cancer had a better response to immune checkpoint therapy, which could be NCT, national clinical trial; OS, overall survival; PFS, progression-free survival; TNBC, triple negative breast cancer; HER2+, human epidermal growth factor receptor 2 overexpression.…”
Section: Discussionmentioning
confidence: 96%
“…[47][48][49] The immune microenvironment can exert great influence on the progression of breast cancer, which results in the different clinical prognosis of patients. [50][51][52] We found that patients with TNBC and HER2 overexpression breast cancer had a better response to immune checkpoint therapy, which could be NCT, national clinical trial; OS, overall survival; PFS, progression-free survival; TNBC, triple negative breast cancer; HER2+, human epidermal growth factor receptor 2 overexpression.…”
Section: Discussionmentioning
confidence: 96%
“…Singlecell RNA sequencing of breast cancer has confirmed that there is a complex mixture of immune T cell subtypes in tumors (6,7). Besides, a large number of transcriptomics analyses have been used to explore the immune microenvironment of breast cancer, which indicated that patients with different expression of genes involving multiple immune cells had different survival rates (8)(9)(10)(11). Most of the previous research methods to decipher the characteristics of tumor immune microenvironment infiltration were based on the transcriptome (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a large number of transcriptomics analyses have been used to explore the immune microenvironment of breast cancer, which indicated that patients with different expression of genes involving multiple immune cells had different survival rates (8)(9)(10)(11). Most of the previous research methods to decipher the characteristics of tumor immune microenvironment infiltration were based on the transcriptome (8,9). DNA methylation, RNA and protein levels can be used as prognostic markers (12).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Li et al reported both immune-reduced and immune-enhanced subtypes with differing immune-related and clinical characteristics to provide targets for new treatments [23]. For breast cancer, Zheng et al developed an immune phenotype classifier for predicting both immune activity within the tumor microenvironment and prognoses for patients with triple-negative breast cancer [24]. In addition, numerous investigations have been conducted using immune subtypes to predict clinical prognoses and treatment guidance for bladder cancer [25], ovarian carcinoma [26], uveal melanoma [27], lung cancer [28,29], and head and neck cancers [30].…”
Section: Discussionmentioning
confidence: 99%